Training on Nearpod Implementation to Enhance Students Engagement and Prepare Gen-Z Pre-Service Teachers to Be Interactive and Innovative - Arniwati Gulo; Puspa Triyani Waruwu; Yurman Ziliwu; Yasminar Amaerita Telaumbanua (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The Nearpod Implementation Training, attended by ten students from the Indonesian Language Education Study Program was conducted, with the aim of enhancing student engagement in learning and preparing gen-z pre-service teachers to become interactive and innovative educators. this activity was designed based on students’ needs for improved digital literacy and pedagogical competence in designing technology-integrated learning. the method included need identification, in-person training, demonstration of Nearpod features, and hands-on practice in creating interactive learning content. The training evaluation used three instruments: a training evaluation questionnaire, field notes, and a participant assessment rubric. the results revealed significant improvements in five key areas: technological proficiency, student engagement strategies, confidence in digital teaching, creativity, and peer collaboration. Participants with diverse technological backgrounds were able to show meaningful progress due to the inclusive and interactive training approach. these findings emphasize the importance of strengthening pre-service teachers’ competencies through participatory digital tools like Nearpod to address the challenges of 21st century learning.